A review of the History of Spine Surgery in Greece until the Middle of the 20th Century - Konstantinos Markatos; Gregory Tsoucalas; Maria K Kaseta; Demetrios S Korres; Georgios Androutsos; Nikolaos Efstathopoulos; Vassilios Nikolaou (Journal of Research on History of Medicine, 2014)
Spine Surgery began its evolution in the beginning of the 19th century in order to reach nowadays the point of being considered an important subspecialty of Neurosurgery and Orthopaedics. The purpose of this historical review is the search and evaluation of the progress in spine surgery until the middle of the 20th century. This review concerns the inauguration and evolution of this field in Greece. Special references are made to the first achievements of this field, to the pioneers physicians and surgeons (general surgeons, orthopaedic surgeons and neurosurgeons) who inaugurated this subspecialty and to clinical and scientific work of that era. Eventually, the progress of medicine and technology who led to the first achievements of this subspecialty are shown and also the difficulties (both social and scientific) that the pioneers of this field faced are demonstrated. In Greece, with small exceptions, the new techniques emerged with a certain delay.